Patient and Parent Satisfaction with a Dietitian-and Nurse-Led Celiac Disease Clinic for Children at the Stollery Children’S Hospital, Edmonton, Alberta - Seema Rajani; Jessica Sawyer-Bennett; Leanne Shirton; Gail DeHaan; Cheryl Kluthe; Rabindranath Persad; Hien Q Huynh; Justine Turner (Canadian Journal of Gastroenterology)
OBJECTIVE: To assess patient and parent satisfaction with a primarily nurse- and dietitian-led celiac disease clinic in a tertiary pediatric centre.